Country data profile: Togo - Transform Nutrition West Africa (International Food Policy Research Institute, 2019)
The purpose of this data profile is: 1) To summarize all available primary data sources and secondary data aggregation platforms for key nutrition indicators representative at the national level in Togo. 2) To assess the identified data sources for each indicator across four dimensions: (i) validity and comparability, (ii) timeliness, (iii) accessibility, and (iv) representativeness. 3) To identify data gaps in the national data system to effectively track progress on nutrition and/or inform policy and program decisions for improving nutrition in Togo.